TI_GERICHTE 12.2009.79 vom 14. Oktober 2009 , Lavoro. licenzimaento immediato giustificato per insulti a superiore - TI Tribunale d'appello (2009)
Lavoro. licenzimaento immediato giustificato per insulti a superiore